Cellular senescence in renal ischemia-reperfusion injury - Ying Chen; Li Yang; Sihan Zhou (Chinese Medical Journal)
Abstract. Acute kidney injury (AKI) affects more than 20% of hospitalized patients and is a significant contributor to morbidity and mortality, primarily due to ischemia-reperfusion injury (IRI), which is one of the leading causes of AKI. IRI not only exacerbates the immediate impact of AKI but also facilitates its progression to chronic kidney disease (CKD) and, in cases of preexisting CKD, to end-stage renal disease (ESRD). One of the critical pathological processes associated with IRI-AKI is cellular senescence, characterized by an irreversible arrest in the cell cycle, morphological and chromatin organization changes, altered transcriptional and metabolic profiles, and the development of a hypersecretory phenotype known as the senescence-associated secretory phenotype (SASP). The SASP amplifies senescence signals in surrounding normal cells through senescence-related pathways, contributing to tissue damage, fibrosis, and chronic inflammation. This review provides an overview of the defining features of senescent cells and explores the fundamental mechanisms underlying senescent cell generation following IRI. We elucidate the pivotal roles of cellular senescence in the transition from IRI-AKI to chronic kidney injury. Furthermore, we discuss emerging therapies targeting cellular senescence, including senolytics and senomorphics, which have shown promising results in both preclinical and clinical settings. These therapies position cellular senescence as a crucial target for the treatment of IRI in the kidneys. Additionally, advancements in single-cell sequencing technology and artificial intelligence-assisted drug screening are expected to accelerate the discovery of novel senescent biomarkers and synotherapeutics, paving the way for optimized and personalized therapeutic interventions.